1987
DOI: 10.1103/physrevb.35.3496
|View full text |Cite
|
Sign up to set email alerts
|

Hamiltonian dynamics of the double sine-Gordon kink

Abstract: We present a complete Hamiltonian treatment of a kink with an internal degree of freedom, namely the double sine-Gordon (DSG) kink. In this formalism we assign two canonical coordinates and their associated momenta to describe the motion of the center of mass of the DSG kink and the relative motion of its two subkinks. We show that the canonical coordinate representing the separation of the two subkinks describes a nonlinear oscillatory degree of freedom. Consequently, the DSG kink behaves like a "molecule" (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The parameter R(t) in [7a] and [7b] is now to be promoted to a dynamical variable R(t) in order to proceed with the development of a Hamiltonian formalism in which it becomes a canonical coordinate (8). The time derivative of (7) is…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameter R(t) in [7a] and [7b] is now to be promoted to a dynamical variable R(t) in order to proceed with the development of a Hamiltonian formalism in which it becomes a canonical coordinate (8). The time derivative of (7) is…”
Section: Discussionmentioning
confidence: 99%
“…In this note, we shall treat, in terms of the Hamiltonian dynamic theory without the corrective terms of the first order, i.e., the radiation correction (8,9), the internal oscillations of three kinks in the double SGE with n = 3, and show that there is an exact stationary solution for the equation. The frequencies and the ratio between the frequencies of the internal oscillations are calculated.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is possible to find a topologically stable 2π-kink solution for a range of parameter η, i.e., η > −1/4. For η ≥ 0, the 2π-kink solution can be constructed by a superposition of π-kink solutions when η → ∞, i.e., φ π (x) = 2 tan −1 exp(x) [9,10,11,12], and expressed as…”
Section: Double Sine-gordon Equation For Long Sfs Junctionmentioning
confidence: 99%
“…With a dynamical π-π kink pair, these two energies compete in time, resulting in a new type of dynamics. The π-π kink pair exhibits an internal oscillation related to the relative oscillations of two π kinks around the equilibrium separation [9,10,11,12]. It has been shown that the frequency of the π-π kink oscillation is below the lower edge of the continuum phonon band [10,13].…”
Section: Double Sine-gordon Equation For Long Sfs Junctionmentioning
confidence: 99%
See 1 more Smart Citation